Biblija in antični mit v pesmih Czesława Miłosza - Unuk, Jana (Primerjalna književnost, 2008)
This article discusses the ancient mythical motifs and most frequent biblical motifs in the poems of Czesław Miłosz. Using the "grammar of literary archetypes" developed by Northrop Frye, these poems are divided into those connected with metaphors from Genesis and those derived from the two poles of apocalyptic metaphors.
Keywords: Miłosz, Czesław, 1911-2004; poljska poezija; modernizem; antična mitologija; biblijski motivi; literarni arhetipi